Fishes of the genus Lutianus off the East African coast - Talbot, Frank Hamilton (Department of Biological Sciences, 2017)
Volume 1. Fishes of the genus Lutianus off the East African coast. Volume 2. Notes on the biology of the Lutjanids of the East African coast. Volume 3. The coral structure of Tutia reef and its fish fauna. Volume 4. Supporting papers